Bone repair with raloxifene and bioglass nanoceramic composite in animal experiment - Lisboa-Filho, Paulo N. [UNESP]; Gomes-Ferreira, Pedro Henrique S. [UNESP]; Batista, Fábio R. S. [UNESP]; Momesso, Gustavo A. C. [UNESP]; Faverani, Leonardo P. [UNESP]; Okamoto, Roberta [UNESP] (Taylor & Francis, 2018)
OBJECTIVE: This study proposes to evaluate, by means of microtomographic analysis, the topical potential of raloxifene combined with BioGran® through the sonochemical method in the repair of critical bone defects in the calvaria of rats. The hypothesis was that the homogenization of Raloxifene to Biogran at the 20% concentration would improve the bone repair at the grafted site. MATERIALS AND METHODS: A 5-mm calvaria bone defect was induced in three groups: CTR (100% BioGran®); RAL10 (90% BioGran® and 10% raloxifene), and RAL20 (80% BioGran® and 20% raloxifene). The animals were euthanized after 30 days and the microCT analysis was then performed to evaluate the parameters bone volume (BV), bone volume percentage (BV/TV), trabecular bone thickness (Tb.Th), and the separation and number of trabeculae (Tb.Sp and Tb.N). The obtained results were compared using ANOVA and Tukey test (p < 0.05). RESULTS: The best results were found for the CTR and RAL20 groups, in which the BV, BV/TV, Tb.Sp, and Tb.N parameters were statistically significant in comparison with RAL10 (p < 0.05). CONCLUSIONS: In view of the results obtained in this experiment, we can conclude that BioGran® alone or in an 80/20 mass concentration with raloxifene can lead to favorable bone formation.
Keywords: Bioglass; Biomaterials; Calvaria; in vivo experiment; osteoporosis; raloxifene; Raloxifene